Islamic Banks Stability in Indonesia: Assesing the Role of Islamicity Performance Amidst the Pandemic Challenges - Siti Amaroh; Ely Masykuroh; Husnurrosyidah Husnurrosyidah; Maimunah Ali (ETIKONOMI, 2024)
Research Originality: Islamicity performance reflects adherence to Sharia principles, which are fundamental to Islamic banking operations. Research that emphasizes the contribution of Islamicity performance to the stability of Islamic bank requires additional studies.Research Objectives: This research examines the influence of banks’ internal factors, Islamicity performance, and macroeconomic factors on the Islamic bank stability amidst the pandemic challenges using financial intermediation theory.Research Methods:A random effects test was performed on a balanced panel data covering the period of 2017.1-2023.3 on 10 Islamic banks continuously publishing quarterly financial reports.Empirical Results: Credit risk and eficiency affect stability. Higher expenses enhance stability during pandemic. Reserves for uncollectible debt reduce stability. Islamicity performance in profit-sharing financing may reduce stability. Economic growth and inflation negatively affect stability pre-pandemic. Interest rate and dummy variables have positive effects.Implications: These findings imply the significance of preemptive risk management, cost-effective operations, prudent reserves allocation, and regulatory compliance to enhance stability in Islamic bank across varying economic circumstances.JEL Classification: E4, G21, B22How to Cite:Amaroh, S., Masykuroh, E., Husnurrosyidah., & Ali, M., (2024). Islamic Banks Stability in Indonesia: Assesing the Role of Islamicity Performance Amidst the Pandemic Challenges. Etikonomi, 23(2), 317 – 332. https://doi.org/10.15408/etk.v23i2.37269.